ANALISIS GAYA BELAJAR PESERTA DIDIK KELAS X PADA MATERI PENCEMARAN AIR DENGAN MODEL PROJECT BASED LEARNING (PjBL) - Nabila; Ie, Johanes Juan Yutama Putra (Universitas Cokroaminoto Palopo, 2025)
Identifying learners' learning styles is a major part of supporting better learning. Knowing the learning style of students is very important to develop meaningful learning. This study aims to analyze the learning style of class X students on water pollution material through the application of the Project Based Learning (PjBL) model. This research was conducted at SMA Karya Dharma Veteran Sambi, Boyolali. The research method used was descriptive qualitative with data collection techniques in the form of questionnaires, interviews, and observations. Data analysis was carried out by percentage analysis and interview analysis techniques using Miles and Huberman techniques, including data collection, data reduction, data presentation and conclusion drawing. The results showed that students have different learning style tendencies, with visual learning styles dominating. The application of the PjBL model in learning water pollution material has a positive impact on improving student learning outcomes, as evidenced by the N-gain result of 0.55 in the moderate category. The PjBL learning model was able to accommodate the learning style needs of students by combining discussion, lecture, and practicum methods.